Broadband Two-Color Laser-Induced Incandescence Pyrometry Approach for Nanoparticle Characterization with Improved Sensitivity. Issue 9 (September 2013) - Flügel, Alexandre; Kiefer, Johannes; Will, Stefan; Leipertz, Alfred
A spectral filtering approach for improving the sensitivity of two-color laser-induced incandescence measurements is proposed. The commonly used bandpass filters providing wavelength selection, and hence temperature sensitivity, are replaced by shortpass and longpass filters, respectively, allowing significantly higher signal intensities to be detected. This modification is of particular interest when nanoparticles with low emissivity, for instance, metal and metal oxide particles, are investigated. An example case in which the conventional optical components are compared with the new approach reveals an improvement by more than one order of magnitude.